Cerebrospinal Fluid, Brain Electrolytes Balance, and the Unsuspected Intrinsic Property of Melanin to Dissociate the Water Molecule - Herrera, Arturo Solís; Ashraf, Ghulam M.; del Carmen Arias Esparza, María; Tarasov, Vadim V.; Chubarev, Vladimir N.; Avila-Rodriguez, Marco F.; Makhmutovа, Alfiya; Ganash, Magdah; Mosa, Osama F.; Hafeez, Abdul; Bachurin, Sergey O.; Aliev, Gjumrakch (CNS & Neurological Disorders - Drug Targets, 2018)
Background & Objective: Regulation of composition, volume and turnover of fluids surrounding the brain and damp cells is vital. These fluids transport all substances required for cells and remove the unwanted materials. This regulation tends to act as barrier to prevent free exchange of materials between the brain and blood. There are specific mechanisms concerned with fluid secretion of the controlled composition of the brain, and others responsible for reabsorption eventually to blood and the extracellular fluid whatever their composition is. The current view assumes that choroidal plexuses secrete the major part of Cerebrospinal Fluid (CSF), while the Blood-Brain Barrier (BBB) has a much less contribution to fluid production, generating Interstitial Fluid (ISF) that drains to CSF. The skull is a rigid box; thereby the sum of volumes occupied by the parenchyma with its ISF, related connective tissue, the vasculature, the meninges and the CSF must be relatively constant according to the Monroe-Kellie dogma. This constitutes a formidable challenge that normal organisms surpass daily. The ISF and CSF provide water and solutes influx and efflux from cells to these targeted fluids in a quite precise way. Microvessels within the parenchyma are sufficiently close to every cell where diffusion areas for solutes are tiny. Despite this, CSF and ISF exhibit very similar compositions, but differ significantly from blood plasma. Many hydrophilic substances are effectively prevented from the entry into the brain via blood, while others like neurotransmitters are extremely hindered from getting out of the brain. Anatomical principle of the barrier and routes of fluid transfer cannot explain the extraordinary accuracy of fluids and substances needed to enter or leave the brain firmly. There is one aspect that has not been deeply analyzed, despite being prevalent in all the above processes, it is considered a part of the CSF and ISF dynamics. This aspect is the energy necessary to propel them properly in time, form, space, quantity and temporality. Conclusion: The recent hypothesis based on glucose and ATP as sources of energy presents numerous contradictions and controversies. The discovery of the unsuspected intrinsic ability of melanin to dissociate and reform water molecules, similar to the role of chlorophyll in plants, was confirmed in the study of ISF and CSF biology.
Keywords: photosynthesis